A Multicenter Collaborative to Reduce Unnecessary Care in Inpatient Bronchiolitis - Ralston, Shawn L; Garber, Matthew D; Rice-Conboy, Elizabeth; Mussman, Grant M; Shadman, Kristin A; Walley, Susan C; Nichols, Elizabeth (Pediatrics (Evanston), 2016)
Evidence-based Guidelines for acute viral bronchiolitis recommend primarily supportive care, but unnecessary care remains well documented. Published quality improvement work has been accomplished in children's hospitals, but little broad dissemination has been reported outside of those settings. We sought to use a voluntary collaborative strategy to disseminate best practices to reduce overuse of unnecessary care in children hospitalized for bronchiolitis in community settings. This project was a quality improvement collaborative consisting of monthly interactive webinars with online data collection and feedback. Data were collected by chart review for 2 bronchiolitis seasons, defined as January, February, and March of 2013 and 2014. Patients aged <24 months hospitalized for bronchiolitis and without chronic illness, prematurity, or intensive care use were included. Results were analyzed using run charting, analysis of means, and nonparametric statistics. There were 21 participating hospitals contributing a total of 1869 chart reviews to the project, 995 preintervention and 874 postintervention. Mean use of any bronchodilator declined by 29% (P = .03) and doses per patient decreased 45% (P < .01). Mean use of any steroids declined by 68% (P < .01), and doses per patient decreased 35% (P = .04). Chest radiography use declined by 44% (P = .05). Length of stay decreased 5 hours (P < .01), and readmissions remained unchanged. A voluntary collaborative was effective in reducing unnecessary care among a cohort of primarily community hospitals. Such a strategy may be generalizable to the settings where the majority of children are hospitalized in the United States.